Thalictrum bouffordii (Ranunculaceae), a new species from the Qionglai mountains region in western Sichuan, China - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2021)
Thalictrum bouffordii (Ranunculaceae), a new species from the Qionglai mountains region in western Sichuan, China, is illustrated and described. Morphologically T. bouffordii is most closely similar to T. xinningense in habit and having clavate filaments, apically recurved styles, and sessile, profoundly ribbed and pubescent achenes, but differs by having proximally glabrous (vs. densely pubescent) stem, inflorescence a many-flowered corymbiform compound monochasium (vs. a thyrse), abaxially pubescent (vs. glabrous) sepals, and purplish (vs. white) filaments.